PENGARUH MARGIN LABA BERSIH, RASIO LANCAR DAN PERPUTARAN TOTAL AKTIVA TERHADAP HARGA SAHAM PADA PERUSAHAAN SEKTOR CONSUMER GOODSINDUSTRY YANG TERDAFTAR DI INDONESIA STOCK EXCHANGE - Gulo, Novita; Purba, Dianty Putri; Situmorang, Rosdiana; Anggraini, Agustina (JURNAL GLOBAL MANAJEMEN, 2019)
This research aimed at testing and analyzing the effect of Net Profit Margin, current ratio, and Total asset turn over on the stock price of companies in consumer goods industry sector which were listed in Indonesia Stock Exchange in 2014-2018 period. This research was done because there were different findings in one previous research and another previous research. This research applied Double Linear Regression Analysis with quantitative method. The variables used by the researcher were Net Profit Margin, current ratio, and Total asset turn over on stock price. The type of data used in this research was secondary type data while the technique of collecting data applied documentation technique through published journals and reports and financial statements of the companies in consumer goods industry sector which were listed in Indonesia Stock Exchange in 2014-2018 period.